The influence of self-compassion on flourishing with growth mindset as a moderator variable in Sleman Regency collage students - Emilia Valkha Agustina; Maharani Tyas Budi Hapsari (Jurnal Psikologi Tabularasa, 2025)
Students in Sleman Regency often experience academic pressure that can lead to stress and burnout, affecting their psychological well-being. Such conditions impact both mental health and students’ academic and social functioning in higher education. This study aims to investigate the influence of self-compassion on flourishing and to examine the moderating role of growth mindset in this relationship. Employing a quantitative research design, data were collected from 132 students in Sleman Regency selected through purposive sampling. The instruments used included the Self Compassion Scale, Flourishing Scale, and Growth Mindset Scale. Data analysis was performed using moderated regression analysis. The results were obtained from the analysis using moderated regression analysis with a correlation coefficient value (r) of 0.035 (<0.05) The results showed that self compassion had a significant positive influence on flourishing, and the growth mindset not be able to moderated the relationship significantly. Growth mindset moderation of the relationship between flourishing and self-compassion was not significant (Z = −0.929, p = 0.353, 95% CI [−0.287,0.0941]). These findings indicate that growth mindset functions more as a mediating mechanism than as a factor that strengthens or weakens the relationship between flourishing and self-compassion.